2009
DOI: 10.1007/s10704-009-9320-0
|View full text |Cite
|
Sign up to set email alerts
|

The stress and strain concentrations of an elliptical hole in an elastic plate of finite thickness subjected to tensile stress

Abstract: The elastic stress and strain fields in a plate of finite thickness containing an elliptical hole are systematically investigated using the 3D finite element method. It is found that the stress and strain concentrations are different in the plate of finite thickness even if the plate is in an elastic state. The relation between the stress and the strain concentration factors depends on Poisson's ratio, the hole's geometric configuration and the plate thickness. The stress concentration factor is equal to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 11 publications
3
12
0
Order By: Relevance
“…The finite element models presented in this paper is justified by referring to the theoretical values of K t extracted from works of Pilkey (2008), Petersen (1974) and conclusion offered by Yang (2009). According to Yang (2009), stress concentration factors for 2-D designs are in good agreement with 3-D designs as long as the thickness of the geometry in kept small enough. Based on this comment, the thickness and diameter of the finite element models analyzed in this paper were kept considerably small.…”
Section: Verification Of Finite Element Modelmentioning
confidence: 81%
See 2 more Smart Citations
“…The finite element models presented in this paper is justified by referring to the theoretical values of K t extracted from works of Pilkey (2008), Petersen (1974) and conclusion offered by Yang (2009). According to Yang (2009), stress concentration factors for 2-D designs are in good agreement with 3-D designs as long as the thickness of the geometry in kept small enough. Based on this comment, the thickness and diameter of the finite element models analyzed in this paper were kept considerably small.…”
Section: Verification Of Finite Element Modelmentioning
confidence: 81%
“…Yang (2009) showed that the plane stress condition of 3D models is approximately achieved by the 2D ones when the plate thickness tends to zero. Zhao et al (2008) is a summarized the 3D effect of stress concentrations at notches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the micro-stress concentrations in the orthotropic plates were calculated, considering the boundary conditions. [5,[8][9][10][11][12] The results were dependent on the internal shape of the plate and the volume ratio of the components. In this section, the finite element modelling and analysis of micro structure for a composite plate with a circular hole for unidirectional fibres using ANSYS is discussed.…”
Section: Micro-stress Concentration While Applying Uniform Normal Prementioning
confidence: 99%
“…Experimental results of the tensile strain field around circular hole in a composites plate by Toubal et al [8] were compared with the predictions of a theoretical model previously developed by Lekhnitskii and a finite element study. For a plate containing a hole that is subjected to uniaxial tension or out-of-plane bending, the sensitivity of the stress and strain concentration factors to plate thickness as well as the Poisson's ratio or moment ratio were done by Yang et al [9,10] and Yang [11]. Rhee et al Moreover, [12,13] examined extensive experimental and numerical studies for determining the stress concentration around circular, elliptical holes in composite infinite plate subjected to arbitrary uniaxial and biaxial loading at infinity using finite method obtained in works.…”
Section: Introductionmentioning
confidence: 99%